Capable environments. Issue 3 (26th November 2020) - McGill, Peter; Bradshaw, Jill; Smyth, Genevieve; Hurman, Maria; Roy, Ashok
Abstract : Purpose: The purpose of this paper is to outline the role played by different aspects of the social, physical and organisational environments in preventing behaviour described as challenging in people with learning disabilities. Design/methodology/approach: Conceptual elaboration drawing on research and practice literature. Findings: Community placements for people with learning disabilities should develop the characteristics of capable environments. Such characteristics are associated with prevention of challenging behaviour and improved quality of life outcomes. Originality/value: The notion of the capable environment may help to shift the focus from the individual who displays behaviour described as challenging to the characteristics of the social, physical and organisational supports that they receive.